Breast conservation and oncoplastic surgery are associated with improved quality of life - Barbalho, Daniel; Polidorio, Natalia; Mori, Lincon; Barros, Alfredo; Sampaio, Marcelo; Melo, Sandro; Assis, Amilcar; Bioni, Pamela; Miziara, Giovanna; Fraga, Murilo; Andrade, Felipe (Frontiers in Oncology, 2024)
IntroductionLocal treatment can be distressful to breast cancer patients. We aimed to evaluate how different types of local treatment impact the quality of life of patients.MethodsIn this retrospective cohort study, one-year postoperative Breast-Q Satisfaction with Breasts scores were used as a surrogate for Quality of Life. Linear regression was used to estimate the impact of breast conservation, oncoplastic surgery, breast reconstruction, and radiation therapy on Breast-Q scores. All analyses were adjusted for multiple covariates.ResultsOf the 711 eligible patients, 349 female patients answered both the pre- and one-year postoperative questionnaires and were included in the final analysis. In total, 237 (68%) patients underwent breast-conserving surgeries and 112 (32%) underwent mastectomies. All mastectomy patients underwent breast reconstruction and 176 (74% of breast-conserving surgeries) underwent concomitant oncoplastic surgery. After multivariate analysis, mastectomy was associated with lower scores compared to breast-conserving surgery (-21.3; 95%CI: -36.2, -6.4, p=0.005), and oncoplastic surgery was associated with higher scores (9.2; 95%CI: 0.8, 17.6, p=0.032). There was a tendency for higher scores with the use of flaps in breast reconstruction and a tendency for lower scores with the use of radiation therapy, but the difference was not significant.ConclusionsBreast-conserving surgery is associated with better quality of life than mastectomy. Additionally, oncoplastic surgery is associated with a better quality of life than standard breast-conserving surgery. Patients should be counseled whenever multiple options for surgery are possible, and efforts should be made to increase the availability of trained surgeons in oncoplastic techniques.